The Effect of Using Secang (Caesalpinia secang Linn) Infusion on the Organoleptic Quality of Chicken Sausage - Ani Way Ratna; Metha Monica; Sri Arnita Abu Tani (Jurnal Sain Peternakan Indonesia, 2022)
This study aims to determine the effect of using Secang infusion (Caesalpinia secang Linn) on the organoleptic quality of chicken sausages and determine the optimal level of adding Secang infusion on the organoleptic quality of chicken sausages. This research was carried out in 30 days at the Laboratory of the Faculty of Animal Husbandry, University of Jambi. This study used a randomized block design (RBD) which consisted of 4 treatments and 30 replications (panelists). The concentration of Secang infusion used was 0%, 5%, 10%, and 15%. The variables observed in this study were the value of organoleptic quality, which included color, aroma, taste, texture, and elasticity. The data obtained were analyzed by analysis of variance (ANOVA). If it had a significant effect, it continued with Duncan's test. The results showed that the use of Secang infusion on chicken sausage had a very significant effect (P<0.01) on color but had no effect (P>0.05) on aroma, taste, texture, and elasticity. The higher the concentration of  Secang infusion, the more preferred the sausage color will be. It can be concluded that the processing of chicken sausage with the addition of Secang infusion at 10% and 15% level produced the preferred color of the panelist's preference level compared to the 0% and 5% levels. Still, the addition of Secang in the processing of chicken sausage did not make a difference to the level of preference for aroma, taste, texture, and suppleness.